Cordia Myxa Fruit Effect on Bacterial Adhesion to Heat-Cured Acrylic Denture Bases - R. Taha, Noor; M. Abass, Shorouq ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Maintaining clean dentures is crucial for the health of the patients and the dental personnels. This study investigated the antibacterial effect of Cordia Myxa Fruit (CMF) extract on Bacillus subtilis adhesion to heat-cured acrylic denture bases, comparing it to Glutaraldehyde 2%. Forty disc-shaped heat-cured acrylic specimens were divided into four groups: untreated control, Glutaraldehyde 2% immersion for 10 minutes, and in CMF extract at concentrations of 100 mg/ml and 150 mg/ml for 15 minutes. Bacillus subtilis adhesion was assessed by spectrophotometric analysis. Surface morphology was examined using scanning electron microscopy. Statistical analysis included one-way ANOVA and Tukey HSD, statistical significance established at p < 0.05. CMF extract significantly reduced bacterial adhesion compared to the untreated control (p < 0.05). The CMF extract of the 150 mg/ml group showed antibacterial effects comparable to Glutaraldehyde 2%, with no significant difference between them (p > 0.05). Scanning electron microscopy revealed that Glutaraldehyde treatment caused degradation, while CMF-treated specimens maintained surface integrity similar to untreated control. CMF extract demonstrated effective antibacterial activity against Bacillus subtilis, suggesting its potential as a natural, safer alternative to chemical disinfectants in dental practice.